Increased Regulatory T Cells in Peripheral Blood of Acute Myeloid Leukemia Patients Rely on Tumor Necrosis Factor (TNF)-α–TNF Receptor-2 Pathway - Wang, Min; Zhang, Chen; Tian, Tian; Zhang, Teng; Wang, Ruiqing; Han, Fengjiao; Zhong, Chaoqin; Hua, Mingqiang; Ma, Daoxin (Frontiers in Immunology, 2018)
Acute myeloid leukemia (AML) harbors an immune suppression environment, featured by increased regulatory T cells (Tregs). The expression of tumor necrosis factor receptor-2 (TNFR2) on Tregs could be used to identify the maximally suppressive Treg population, and TNF-α furtherly promoted the expansion and function of Tregs via TNFR2 in mice. However, the role of TNF-α has not been determined in AML patients. In view of high levels of TNF-α and Tregs in AML patients, we hypothesized that the increased frequency of Tregs may rely on TNF-α–TNFR2 pathway. We investigated the levels of TNFR2+ Tregs and TNF-α secreted by T cells in peripheral blood (PB) of AML by flow cytometry and enzyme-linked immunosorbent assay, respectively. Our results showed the elevated plasma TNF-α in PB of newly diagnosed (ND) AML patients. The production of TNF-α by CD4+ T cells, especially by T helper (Th)17 cells was remarkably higher in ND AML patients than in complete remission (CR) patients and healthy controls. Then, we found that the circulating frequencies of CD4+CD25+ Tregs and CD4+CD25high Tregs in AML patients were elevated compared with those in healthy controls and CR patients. TNFR2 expression was much higher on Tregs in AML patients and was preferentially expressed on CD4+CD25high T cells. Furthermore, we confirmed that, in vitro, the additional TNF-α can increase the frequency of Tregs through TNFR2 in both AML patients and healthy controls. Summarily, in AML patients, the abnormally elevated level of TNF-α secreted by CD4+ T especially Th17 cells promoted the higher Tregs frequency via the TNF-α–TNFR2 pathway.